Mangrove Ecotourism Development on the Coast of Kabita Village South Wangi-Wangi District Wakatobi Regency - Jamiludin, Nurfitri; Uca, Uca; Hasriyanti, Hasriyanti; Maru, Rosmini; Saud, Syukur (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2024)
This study aims to identify the potential of mangrove ecotourism, and the suitability of mangrove ecotourism and determine mangrove ecotourism development strategies on the coast of Kabita Village, South Wangi-Wangi District, Wakatobi Regency. This research utilized mixed methods: quantitative and qualitative research methods. Data collection was carried out with primary data, namely observation of mangrove areas, questionnaires, and interviews with the people of Dusun II Kabita Village and stakeholders using purposive sampling techniques and secondary data, namely documentation and literature studies. The analysis used in this study is quantitative analysis, qualitative, and SWOT analysis. The results of the analysis of mangrove ecotourism potential show that the mangrove ecosystem of Kabita Village has a thickness of 239.21 m, a density of 0.98 ind/m2, the tidal height reaches 0.2 m/s, there are 4 types of mangroves namely Rhizoppora mucronata, Rhizopora apiculata, Sonneratia alba and Bruguera gymnorrhiza and aquatic biota in the form of birds, crabs, shrimp, various types of mollusks and starfish. Priority strategies are to maintain and always preserve the condition of mangrove vegetation, increase community participation and empowerment, spatial planning of tourist sites and preparation of master plans, training on tourism-related businesses for local human resources, developing mangrove areas as ecotourism areas by cooperating with BUMN, private sector, and surrounding communities and increasing publications related to the existence of mangrove ecosystems and their protection through Ecotourism development.